2015
DOI: 10.1177/1524838015584356
|View full text |Cite
|
Sign up to set email alerts
|

Aftercare Services for Child Victims of Sex Trafficking

Abstract: The literature highlighted that aftercare service provision for child sex trafficking victims is a new area that needs an evidence base from which policy and practice can be formed. There is great need for further research and better documentation of service provision. While this research provides insight into this area, the gap in literature remains wide. The area of aftercare service provision for children who have been trafficked has experienced phenomenal growth within the last 10 years, and with more rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 31 publications
0
37
0
Order By: Relevance
“…It is important to note that not all trafficking victims are exposed to substances while being trafficked, nor do all trafficking victims develop a substance abuse disorder during or after being trafficked, but substance abuse services should be available if needed. Emergency mental healthcare services focused on delivering trauma‐informed care (Muraya & Fry, ). Three of five residential treatment centers viewed family reunification as a key service contributing to the recovery of DMST survivors.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to note that not all trafficking victims are exposed to substances while being trafficked, nor do all trafficking victims develop a substance abuse disorder during or after being trafficked, but substance abuse services should be available if needed. Emergency mental healthcare services focused on delivering trauma‐informed care (Muraya & Fry, ). Three of five residential treatment centers viewed family reunification as a key service contributing to the recovery of DMST survivors.…”
Section: Discussionmentioning
confidence: 99%
“…Inclusion of programme evaluations in systematic literature reviews is needed to specify the goals which have been set for the legal rights under investigation, to unravel the mechanisms assumed necessary to achieve these goals, and to identify the empirical and theoretical literature on which these assumptions were based. A recent study by Muraya and Fry (2016) provides an example of how this can be accomplished. They reviewed fifteen programme evaluations about aftercare services for child victims of traffickingwhich are a specific type of victim support and aim to adequately treat the negative psychological, social, and physical outcomes of child trafficking.…”
Section: Application Of the Realist Synthesis Approach In Previous Symentioning
confidence: 99%
“…Studies have reported high prevalence of posttraumatic stress disorder (PTSD) symptoms among victims (Hossain et al 2010). Other studies have reported a high rate of depression, self-injury, and suicide attempts among sexually exploited victims (Muraya and Fry 2016;Saewyc et al 2008).…”
Section: Public Health and Psychological Consequences Of Sex Traffickingmentioning
confidence: 99%